2023
DOI: 10.1126/scitranslmed.abn8134
|View full text |Cite
|
Sign up to set email alerts
|

Catheterization of mice triggers resurgent urinary tract infection seeded by a bladder reservoir ofAcinetobacter baumannii

Abstract: The antibiotic-resistant bacterium Acinetobacter baumannii is a leading cause of hospital-associated infections. Despite surveillance and infection control efforts, new A. baumannii strains are regularly isolated from health care facilities worldwide. In a mouse model of urinary tract infection, we found that mice infected with A. baumannii displayed high bacterial burdens in urine for several weeks. Two months after the resolution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 56 publications
(58 reference statements)
1
6
0
Order By: Relevance
“…By comparing AMR genotypes identified by whole-genome analysis of SSI isolates with antimicrobial susceptibility testing results, perioperative antimicrobial administration records, and the composition of individual preoperative resistomes, we found that the complement of resistance genes present in a patient before surgery strongly correlated with resistance traits of subsequent SSI. This observation is consistent with recent studies of urinary tract infection in which recurrent infections were found to be "seeded" from persistent host reservoirs (44) and in which emergence of AMR after treatment of initially susceptible infections was driven by selection of resistant strains already present in the host rather than newly evolved through de novo mutation or acquired through horizontal gene transfer (45). In our study, sampling of multiple patient reservoirs provided the greatest diagnostic sensitivity for preoperative detection of AMR genes that later contributed to prophylaxis-resistant infection, with the skin overlying the surgical site having the highest diagnostic yield of any single sampling location.…”
Section: Discussionsupporting
confidence: 92%
“…By comparing AMR genotypes identified by whole-genome analysis of SSI isolates with antimicrobial susceptibility testing results, perioperative antimicrobial administration records, and the composition of individual preoperative resistomes, we found that the complement of resistance genes present in a patient before surgery strongly correlated with resistance traits of subsequent SSI. This observation is consistent with recent studies of urinary tract infection in which recurrent infections were found to be "seeded" from persistent host reservoirs (44) and in which emergence of AMR after treatment of initially susceptible infections was driven by selection of resistant strains already present in the host rather than newly evolved through de novo mutation or acquired through horizontal gene transfer (45). In our study, sampling of multiple patient reservoirs provided the greatest diagnostic sensitivity for preoperative detection of AMR genes that later contributed to prophylaxis-resistant infection, with the skin overlying the surgical site having the highest diagnostic yield of any single sampling location.…”
Section: Discussionsupporting
confidence: 92%
“…We recently demonstrated that the clinical isolate UPAB1 establishes small intracellular reservoirs, known as ABIR ( A. baumannii intracellular reservoirs) in bladder epithelial cells of mice that previously cleared a urinary tract infection. We observed that these ABIRs likely act as reservoirs that can be activated upon insertion of a medical device, such a catheter, leading to a resurgent infection in mice (Hazen et al, 2023). It is tempting to speculate that intracellular A. baumannii in AMs may also function as reservoirs in the host.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, given that A. baumannii can establish intracellular reservoirs within bladder epithelial cells, patients with a history of A. baumannii cystitis may benefit from vaccination to prevent recurrence. 9 However, perhaps the greatest potential benefit of an A. baumannii vaccine lies in the developing world. The highest relative burden of deaths associated with antibiotic-resistant A. baumannii occurs in low and middle income countries.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Several single-center studies have identified A. baumannii as a leading cause of CAUTI in their facilities. 8 , 9 Indeed, recent studies have demonstrated that 17% of published A. baumannii isolates originated in the urinary tract and up to 2% of the healthy population may exhibit A. baumannii asymptomatic bacteriuria. 10 , 11 At the same time, the level of antimicrobial resistance identified in A. baumannii isolates is on the rise, with most isolates resistant to at least one antibiotic class and many isolates displaying multi-drug resistance.…”
Section: Introductionmentioning
confidence: 99%